ANALISIS PENDEKATAN KEPEMIMPINAN: SIFAT, TINGKAH LAKU, DAN KONTINGENSI SI SMP NEGERI 27 KABUPATEN KERINCI - Hasimi Jafar; Jamrizal; Minnah El Widdah (STKIP Subang, 2023)
This research discusses the approach of Nature, Behavior, Contingency leadership applied by the Head at SMP Negeri 27 Kerinci. The purpose of this study is useful to describe the leadership approach carried out and applied by the Principal. In this study, the method used is a case study with a qualitative approach. The techniques used in data collection are through observation and interviews. The main resource person in this study was the Head of SMPN 27 Kerinci. In addition, as information or supporting data in this study, namely researching three teacher councils of SMPN 27 Kerinci. The resulting research results are knowing the approach to Nature, Behavior, and Contingency leadership carried out by the Principal. The approach of Nature, Behavior, Leadership contingency carried out by the Principal of SMPN 27 Kerinci is by using a friendly nature approach, namely leaders who have friendliness towards their subordinates. The behavioral approach is disciplined behavior, namely, a leader who is disciplined in obeying the rules that have been set. While the contingency approach is a leader who can adapt to any situation and conditions in the field